CORPS EN SOUFFRANCE / CORPS EN VACANCES. L’ÉCRIVAIN M. BLECHER ET LA PEINTRE LUCIA DEM. BĂLĂCESCU DANS LE SANATORIUM DE TEKIRGHIOL - TUDURACHI, Ligia (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
Suffering bodies/ bodies on vacation. Writer M. Blecher and painter Lucia Dem. Bălăcescu in the Tekirghiol sanatorium. What we propose is an analysis of the creative sharing that two artists, M. Blecher and Lucia Dem. Bălăcescu, both suffering from a bone disease, developed it during their joint hospitalization in the C.T.C sanatorium in Tekirghiol for a year, in 1933-1934. The characteristic of this space is the presence of over 300 children, the sanatorium only exceptionally housing adults. From these children, who have their own way of using play and toys to hide their illness, the two artists learn a childlike way of living their own suffering and feel suggested to cultivate (and) forms of a miniature art. Lucia Dem. Bălăcescu makes a series of 50 mini-gouaches, which he calls Surrealist Fantasies. Blecher, like Robert Walser did in the same years, fantasizes about a miniature writing, designing drawings whose lines are made up of small words to the limit of illegibility.